Bilateral Same-day Laser Peripheral Iridotomy in the Philadelphia Glaucoma Detection and Treatment Project. Issue 10 (October 2016) - Waisbourd, Michael; Shafa, Anousheh; Delvadia, Radha; Sembhi, Harjeet; Molineaux, Jeanne; Henderer, Jeffery; Pizzi, Laura T.; Myers, Jonathan S.; Hark, Lisa A.; Katz, L. Jay
Abstract : Purpose: To report the outcomes of bilateral, same-day laser peripheral iridotomy (LPI) in the Philadelphia Glaucoma Detection and Treatment Project. Methods: The Philadelphia Glaucoma Detection and Treatment Project was a community-based initiative aimed to improve detection, management, treatment, and follow-up care of individuals at high risk for glaucoma. This novel project performed LPI, where 2 eyes received laser therapy on the same day. Of the 1649 patients examined between January 1, 2013 and May 31, 2014, patients who underwent bilateral, same-day LPI were included in our analysis. Main outcome measures were visual acuity, intraocular pressure (IOP), and postoperative complication rates. Results: A total of 132 eyes of 66 patients underwent bilateral, same-day LPI. Mean visual acuity remained unchanged following treatment ( P =0.85). Eight patients (12.1%) had IOP spikes >5 mm Hg following treatment, and 4 patients (6.1%) spiked >10 mm Hg. IOP returned to normal in all but 1 patient, who was diagnosed with chronic angle-closure glaucoma. Hyphema was reported in 2 patients (3%) and glare in 1 patient (1.5%). Thirteen patients (19.7%) had repeat LPI treatment. All patients successfully tolerated LPI treatment without serious complications. Conclusions: Performing bilateral, same-day LPI was well tolerated in a large community-based, glaucoma detection and treatment project. Applying this treatment strategy may be considered in similar settings, where patients' access to eye care is limited and it may be a cost-effective strategy.